Post-Conflict Amnesty Policies of President Goodluck Jonathan in Nigeria: Role of History and Failure of Wrong Philosophies - Ugwu, Ude; Igbede, Moko Finian (Advances in Social Sciences Research Journal, 2014)
This research paper has been titled, “Post-Conflict Amnesty Policies of President Goodluck Jonathan in Nigeria’, The Role of History and the Failure of Wrong Philosophies”. The Central argument of the research was that it is clearly unthinkable to grant another amnesty in Nigeria while an earlier grant of Post-Conflict amnesty to Niger Delta Militants, continues to indicate a likelihood of a possible return of hostility to the region since the Post-Conflict policy itself was never based on dialogue or any sound philosophy of conflict. The paper made this profound observation that the refusal by Nigerian leaders to engage separatist groups in genuine dialogue, is not the only factor’, Greed, Corruption, and Maladministration, etc, are also responsible for the failure of amnesty policies in Nigeria. Yet, the research aimed to discuss the role played by history and the contributions of wrong philosophies to the failure of Post-Conflict amnesty policies in Nigeria. In this way, the paper was significant in raising these two (2) issues, first, that any post conflict amnesty policy in Nigeria, can only succeed by first overcoming tribal sentiment created by the country’s history of civil war, military rule, amalgamation and colonial favours; and second, if this cannot be achieved, then, President Goodluck Jonathan can only succeed by replacing post conflict amnesty policies with genuine dialogue, being in the opinion of this research that dialogue still remains the best philosophy of conflict for any nation.